1993
DOI: 10.2466/pr0.1993.72.3c.1283
|View full text |Cite
|
Sign up to set email alerts
|

Agoraphobic Behavior in Daily Life: Effects of Social Roles and Demographic Characteristics

Abstract: Agoraphobia is related to demographic characteristics and social roles. To unravel behavioral aspects from demographic characteristics, daily life situations were registered with the Experience Sampling Method for 65 panic patients with and without agoraphobia. Surprisingly, panic patients with and without agoraphobia did not differ as hypothesized in reported frequencies of visits to public places. Panic subjects with agoraphobia did, however, spend significantly more time at home and with their families than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Only a few studies have been conducted in the area of anxiety disorders, a domain in which situational triggers are often of importance in eliciting symptoms. Dijkman-Caes et al (1993) compared behavioural aspects of panic disorder patients with and without agoraphobia and, contrary to expectation, found no difference between groups regarding the amount of time spent in public places. Panic subjects with agoraphobia did, however, spend significantly more time at home and with their families than did panic patients without agoraphobia and normal controls.…”
Section: Phenomenologymentioning
confidence: 87%
“…Only a few studies have been conducted in the area of anxiety disorders, a domain in which situational triggers are often of importance in eliciting symptoms. Dijkman-Caes et al (1993) compared behavioural aspects of panic disorder patients with and without agoraphobia and, contrary to expectation, found no difference between groups regarding the amount of time spent in public places. Panic subjects with agoraphobia did, however, spend significantly more time at home and with their families than did panic patients without agoraphobia and normal controls.…”
Section: Phenomenologymentioning
confidence: 87%
“…This was possible because of the use of the ESM procedure. Previous studies have demonstrated the validity of ESM in psychiatric populations (Barge-Schaapveld, Nicolson, van der Hoop & De Vries, 1995;Delespaul, 1995;Dijkman-Caes, De Vries, Kraan & Volovics, 1993;Kimhy et al, 2009Kimhy et al, , 2006Myin-Germeys et al, 2009Myin-Germeys, van Os, Schwartz, Stone & Delespaul, 2001;Peeters, Berkhof, Delespaul, Rottenberg & Nicolson, 2006; van Os, Linscott, Myin-Germeys, Delespaul & Krabbendam, 2009). …”
Section: Discussionmentioning
confidence: 96%
“…In a study with patients who were diagnosed with panic disorder with or without agoraphobia, the ESM was used to see what their daily lives were like. Neither group differed significantly on the avoidance variables of remaining at home or being with a family member, thus challenging the current diagnostic conceptualizations that rely on patients’ retrospective reports of the avoidance of public places (Dijkman-Caes, DeVries, Kraan, & Volovics, 1993). Mokros (1993) compared adolescents who were diagnosed with depression to a group that was not.…”
Section: ) Divergencementioning
confidence: 93%